CXCL4 promoted the production of CD4+CD25+FOXP3+treg cells in mouse sepsis model through regulating STAT5/FOXP3 pathway. (3rd July 2020) - Xu, Tao; Zhao, Jie; Wang, Xiaolin; Meng, Yan; Zhao, Zhenzhen; Bao, Rui; Deng, Xiaoming; Bian, Jinjun; Yang, Tao
Abstract: Background: CXCL4 plays an essential role in the regulation of multiple immune diseases. However, the underlying role of CXCL4 is still not clear in sepsis. Aim: In the present study, we aimed to investigate the function of CXCL4 in sepsis. Methods: Sepsis model was constructed on mouse. Flow cytometry was used to determine the ratio of CD4 + CD25 + FOXP3 + Treg cells. ELISA assays were used to determine the levels of CXCL4, IL-6, IL-10, and TNF-α respectively. Western blot was used to examine protein contents. Results: Our results suggested that the serum level of CXCL4 was upregulated in patients with sepsis and positively associated with the ratio of human CD4 + CD25 + FOXP3 + Treg cells. To further examine the role of CXCL4 in sepsis, we constructed the mouse sepsis model. Our results indicated that the mouse antibody of CXCL4 treatment reduced the expression of urine creatinine and urea nitrogen in sepsis model. Moreover, the frequency of CD25 + FOXP3 + mouse regulatory T cells (Tregs) cells was decreased in mouse CD4 + T cells in the presence of mouse CXCL4 antibody. Further, the mouse recombinant protein CXCL4 was used to culture normal mouse CD4 + T cells in vitro . Our finding indicated that the recombinant protein CXCL4 promoted the percentage of mouse CD25 + FOXP3 + Treg cells and enhanced the phosphorylation of STAT5 in mouse CD4 + T cells in a dose-dependent manner. However, these effects were significantly reversed by the STAT5 inhibitor ( p  < .001). Conclusion: our findings not only indicated the function and signalling pathway of CXCL4 in CD4 + T cells but also provided novel insight and target in sepsis treatment.